High‐BMI at diagnosis is associated with inferior survival in patients with osteosarcoma: A report from the Children's Oncology Group. Issue 12 (17th August 2013) - Altaf, Sadaf; Enders, Felicity; Jeavons, Elysia; Krailo, Mark; Barkauskas, Donald A.; Meyers, Paul; Arndt, Carola
Abstract Background Body mass index (BMI), at diagnosis has been associated with lower survival and increased toxicity in cancer patients. We analyzed the effect of BMI at diagnosis on therapy related toxicities and outcome in pediatric osteosarcoma patients treated on Children's Oncology Group (COG) trial INT0133. Procedures All patients enrolled on COG‐INT0133 with height, weight and toxicity information were eligible. BMI was expressed as age and gender specific percentiles using height and weight at diagnosis. Patients were classified into high, normal and low BMI groups. Logistic regression models were used to analyze toxicities; Kaplan–Meier curves were created to assess event free (EFS) and overall survival (OAS). Results Seven hundred and ten patients met eligibility criteria. BMI distribution was: 447 normal BMI, 74 low BMI, and 189 high BMI. Renal toxicity was higher in the high BMI group (OR = 2.7, 95% CI 1.2–6.4, P = 0.01) only during one of the courses of therapy. Compared to the normal BMI group, patients with high BMI had significantly worse OAS at 5 years compared to those with normal BMI, 69.7% versus 80.5% (HR = 1.6, 95% CI 1.1–2.2, P = 0.005) and a trend towards worse event‐free survival at 3 years 66.2% versus 75.5% (HR = 1.3 95% CI 0.9–1.8, P = 0.05). There was no difference in EFS or OAS in patients with low BMI compared to patients with normal BMI. Conclusions High BMI at diagnosis is associated with worse OAS in patients with osteosarcoma. No clinically significant differences in toxicity were observed in the various BMI groups. Pediatr Blood Cancer 2013;60:2042–2046. © 2013 Wiley Periodicals, Inc.